Professores de Educação Especial atuando em classe comum: possibilidades e desafios de parcerias colaborativas. - Costa, Luis Gustavo da Silva (Universidade Federal de São Carlos, 2024)
This research aimed to analyze and describe the practices of Special Education teachers and regular classroom teachers with Special Education (PEE) students, who worked collaboratively in regular classrooms in the municipal education system of a small municipality in the interior of the state of São Paulo. This descriptive case-study study was based on the qualitative and quantitative research method. Data collection initially involved semi-structured interviews using questionnaires, including three from the Index for Inclusion questionnaire, field diaries, video recordings, photographs, and more. Initially, the diagnostic phase of the research was conducted in three elementary schools and three early childhood education schools, aiming to attract a larger number of teachers. Twenty-eight teachers participated in the study: 14 Special Education teachers and 14 regular classroom teachers. From the diagnostic phase, it was found that of the 28 teachers participating in the study, 10 had never had any contact with Collaborative Teaching or had heard of it. 18 had contact through lectures and Pedagogical Collective Work Meetings (HTPC), where they provided brief reports or explanations on the topic. However, understandings of Collaborative Teaching varied, as did the pedagogical practices implemented among teachers within the regular classroom. Furthermore, they reported insufficient basic knowledge for implementing Collaborative Teaching, a lack of knowledge of the teaching strategy and their roles within it. However, they believed that they were implementing Collaborative Teaching in some way due to their joint work in the regular classroom, where they dialogued and collaborated with one another. However, 98% of the teachers stated they wanted to deepen their knowledge of Collaborative Teaching, considering that the school context in which they worked facilitated this service; to do so, they needed to learn more about the subject. It was concluded, then, that the teachers were in the initial stage of Collaborative Teaching, possessing prior knowledge, which, in fact, corroborated its implementation. It is worth noting that the municipality had a unique characteristic: the Special Education teachers had degrees in Pedagogy and were Specialists in Special Education, working in the Special Education Program within the regular classroom. Furthermore, the studies presented in this thesis, along with the data collected, enabled the development of Collaborative Teaching in Practice (ECNP), through the Initial Tracking of Collaborative Teaching Implementation, four stages, and the 10 crucial foundations for its successful implementation.
Special Education teachers working in regular classrooms: possibilities and challenges of collaborative partnerships.
Keywords: Educação Especial; Ensino Colaborativo; Coensino; Special Education; Collaborative Teaching; Co-teaching; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade